Analysis of the multi-agent's relationship in collaborative innovation network for science and technology SEMs based on evolutionary game theory. (2019) - Nan, Guangyou; Wei, Jinyu; Hu, Haiju
The construction of a collaborative innovation network for the science and technology small and middle enterprises (SMEs) is an attempt to effectively combine the advantages of science and technology SMEs. In this paper, the evolutionary game theory is used to establish the three party game model including the government, science and technology SMEs, and college and research institutions. Then, the interaction mechanism among them is analysed. On the basis of analysing each party's cost and benefit under different strategic portfolios of three parties, the stable strategy of the evolutionary game is derived. The research results show that the government can effectively mobilise the enthusiasm of enterprises and the college and research institutions by setting up reasonable subsidies or fines for them, and could also influence and promote the cooperation relations between enterprises and the college and research institutions.